The complex between urokinase-type plasminogen activator (uPA) and its type-1 inhibitor (PAI-1) independently predicts response to first-line endocrine therapy in advanced breast cancer - Manders, Peggy; Tjan-Heijnen, Vivianne C. G.; Span, Paul N.; Grebenchtchikov, Nicolai; Geurts-Moespot, Anneke J.; van Tienoven, Doorléne T. H.; Beex, Louk V. A. M.; Sweep, Fred C. G. J. (Thrombosis and Haemostasis, 2004)
It has been shown that urokinase-type plasminogen activator (uPA) and its main inhibitor (PAI-1) have predictive value for therapy success in advanced breast cancer. Levels of the complex between uPA and PAI-1, formed when both molecules are in their active form, might have superior predictive power. Here, we investigate the association between levels of uPA:PAI-1 complex and rate of response to first-line systemic therapy for advanced breast cancer. Tumor tissues of 170 patients with advanced breast cancer were analyzed for uPA:PAI-1 complex concentrations using a quantitative enzyme-linked immunosorbent assay. The patients received either endocrine therapy (n=96) or chemotherapy (n=74) as first-line treatment after diagnosis of advanced disease. Of the endocrine treated patients, those with high levels of uPA:PAI-1 complex showed a shorter progression-free survival (PFS) compared to patients with lower uPA:PAI-1 complex levels (P=0.035). Furthermore, in the multivariate regression analysis a significant lower rate of response to first-line endocrine therapy was found in patients with high uPA:PAI-1 complex levels compared to patients with low uPA:PAI-1 complex levels (odds ratio (OR)=0.27, 95% CI, 0.09–0.59, P=0.018), in addition to the predictive impact of the steroid hormone receptor (ER/PgR) status (OR=2.68, 95% CI, 1.08–6.63, P=0.033). Complex levels did not predict efficacy of chemotherapy in patients with advanced breast cancer. The results show that the plasminogen activation system affects the response to endocrine therapy independent of steroid hormone receptor status and may be of help to further refine the indication for this treatment in individual patients. Further studies are warranted to explain this underlying resistance to endocrine therapy when uPA:PAI-1 levels are high.
Keywords: Advanced breast cancer; plasminogen activator inhibitor type-1; predictive; uPA:PAI-1 complex; urokinase-type plasminogen activator